2012
DOI: 10.3329/akmmcj.v3i2.11690
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoacromial Vessel Based Pectoralis Major Myocutaneous Flap in Oral and Maxillofacial Soft Tissue Defect Reconstruction

Abstract: Pedicled flaps play an important role in cancer treatment centers, particularly in developing and emerging countries. Although different flaps can be used for facial reconstruction but Pectoralis major myocutaneous flap is still considered the workhorse for maxillofacial reconstruction because of simple procedure and high success rate, while other flaps of facial region ranging from pedicled to free flaps require greater surgical skills along with unpredictable results.The aim of this study is to find outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…PMMC flap can be used in wide range of defects in the head and neck region including neck, maxilla and temperoorbital area. Skin paddle can be extended as down as rectus abdominal sheath and the advantage of PMMC is that a very big skin paddle overlying whole of muscle can be elevated [8,9]. Study conducted by Kurse et al it was inferred that PMMC flaps are much suited for reconstruction of large defects [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…PMMC flap can be used in wide range of defects in the head and neck region including neck, maxilla and temperoorbital area. Skin paddle can be extended as down as rectus abdominal sheath and the advantage of PMMC is that a very big skin paddle overlying whole of muscle can be elevated [8,9]. Study conducted by Kurse et al it was inferred that PMMC flaps are much suited for reconstruction of large defects [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…6 Skin paddle can be extended as down as rectus abdominal sheath and the beauty of the PMMC is that a very big skin paddle overlying whole of the muscle can be elevated. 8 Kurse et al recommended that PMMC flap is an appropriate flap for huge defects in head and neck reconstruction particularly when large bulky flap is needed to cover carotid artery. 2,9 Like other myocutaneous flap, it is harvested by single stage reconstructive procedure and does not require flap delay or release.…”
Section: Discussionmentioning
confidence: 99%
“…1,14 Ariyan showed that the flap can be raised as an myocutaneous flap based on pectoral branch of thoracoaromian artery. 1,8 PMMC flap originate from the medial 1 1/2 -2/3 of clavicle, lateral part of entire sternum, adjacent cartilage of first 6 rib, bony portion of 4 th 5 th and 6 th rib and inserted into intertubercular groove of humerous. The action of the PMMC flap is abducts, flexes, and medially rotates arm.…”
Section: Introductionmentioning
confidence: 99%